If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1 = 14x + -49 Reorder the terms: -1 + 5x = 14x + -49 Reorder the terms: -1 + 5x = -49 + 14x Solving -1 + 5x = -49 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -1 + 5x + -14x = -49 + 14x + -14x Combine like terms: 5x + -14x = -9x -1 + -9x = -49 + 14x + -14x Combine like terms: 14x + -14x = 0 -1 + -9x = -49 + 0 -1 + -9x = -49 Add '1' to each side of the equation. -1 + 1 + -9x = -49 + 1 Combine like terms: -1 + 1 = 0 0 + -9x = -49 + 1 -9x = -49 + 1 Combine like terms: -49 + 1 = -48 -9x = -48 Divide each side by '-9'. x = 5.333333333 Simplifying x = 5.333333333
| 2x+3y+5z=1 | | -5+7b+3=33 | | N+13=-4(-5n-8) | | y=4/3-2/3 | | 6x=12.96 | | 2x-3+3x-32=90 | | -8x^2+28xy+60y^2=0 | | 2b-10=3b+21 | | 5x-6=3x+24 | | 8(X+7)-4= | | 8x+4=-11 | | 4a+36=29 | | 3x-(-14)=19 | | -54x=-6 | | 4x^2-4x+1=7 | | x+-5sqrt(x)+6=0 | | 5y-9=4y+6 | | y=5-3(-2) | | 2.25x=15.75 | | .60x+.25=.35x-4 | | c=4.95p+32.50 | | x^2-36x+324=1 | | 2(4-0.3b)=6.5 | | 8x-7=x(A+2B)+A-3B | | .25b+.40b-5=-3 | | 4.9(t)+10(t)-5=0 | | 8x+2x-10=100 | | [(x)(x)]-x=2 | | 25h=-15h-80 | | 3/4+x-2=3/5 | | -x+7(x-5)=-32+7x | | 4x-18=10x+8 |